Expanding the material possibilities of lightweight prefabrication in concrete through robotic hot-wire cutting - form, texture and composition - Pedro Filipe Martins (2015)
In the past years, digital fabrication technologies have enabled renewed explorations into traditional materials, with innovative results. This paper focuses on concrete and on the potentials of a specific technology: robotic hot-wire cutting for the production of expanded polystyrene (EPS) formwork. Academia and industry have explored this process recently but the number of works built with this technology is reduced and the general concrete prefabrication industry has been slow to adopt it. In this context, this paper analyzes the use of EPS in the production of concrete formwork by reviewing its application in contemporary examples. In order to develop a clear assessment of the possibilities of expanding prefabrication in concrete using robotic hot-wire cutting, this paper also documents a set of practical experiments developed in the laboratory, addressing three material challenges: form; texture and composition. This research involved the design, formwork production and casting of concrete elements to explore the limits and characterize the process of robotic hot-wire fabrication in the context of concrete prefabrication. By recognizing the different approaches present in contemporary examples and in the explored practical experiments, we point out the advantages and limitations of using hot-wire cutting, and develop the reasons behind its limited application in practice.